Skills of Using Pedagogical Technologies in Forming Intercultural Communication Competences - Kamola Abdullayevna Shokarimova (Euro Asian Journal Publishing, 2024)
The article examines the formation of intercultural communication competencies in students using effective modern interactive methods in the teaching of intercultural communication. Intercultural communication competence is one of the main didactic-methodical principles of modern foreign language classes. Because language and culture are interconnected, the culture of each nation, that is, its thinking, mentality, rules of etiquette, and values are reflected in the language. For this reason, formation of intercultural competence together with learning foreign languages is a requirement of the time in the content of education. However, the use of effective methods in the process of teaching this subject still remains relevant. The author conducted an experiment on philology students. During the trial period, special attention was paid to the practical application of theoretical knowledge to students, and not only by the teacher, but by involving students in practice. The results of the questionnaire conducted at the end of the experiment showed that the used method was the basis for easy and good mastering of the subjects, formed students' skills of free thinking and independent work. The method recommended in the article can be used in teaching the science of intercultural communication in higher educational institutions
Keywords: Language; culture; intercultural communication